The effect of combination therapy of insulin glargine, metformin, and sitagliptin on insulin secretion, insulin resistance, and metabolic parameters in obese subjects with type 2 diabetes - Beljić-Živković Teodora; Marjanović-Petković Milica; Vuksanović Miljanka; Soldatović Ivan; Kanlić Dobrila; Topalov Drina (Srpski Arhiv za Celokupno Lekarstvo, 2016)
Introduction. A combination of drugs is required for treatment of obese subjects with diabetes, due to multiple pathogenic mechanisms implicated in the development of both diabetes and obesity. Objective. Assessment of the effect of sitagliptin added to insulin glargine and metformin, in obese subjects with type 2 diabetes. Methods. A total of 23 obese subjects on metformin and insulin glargine participated in the study. Titration of insulin glargine during a one-month period preceded the addition of 100 mg of sitagliptin daily. Body mass index, waist circumference, fasting, and prandial glucose were measured monthly, lipids and hemoglobin A1c (HbA1c) every three months, insulin, c-peptide and glucagon at the start and after six months of treatment. Homeostatic models for insulin secretion (HOMA B) and insulin resistance (HOMA IR) were calculated. Results. Participants were 58.65 Ѓ} 7.62 years of age with a body mass index of 35.06 Ѓ} 5.15 kg/m2, waist circumference of 115.04 Ѓ} 15.5 cm, and the duration of diabetes of 4.11 Ѓ} 2.57 years. With the titration of insulin glargine, target fasting glucose levels were not achieved. Waist circumference and body mass index decreased during three months of sitagliptin treatment, thereafter remaining stable. HbA1c decreased significantly after three and six months of therapy. C-peptide increased significantly, while glucagon level fell. HOMA indexes were unchanged. Conclusion. Sitagliptin can improve diabetes control and induce modest weight loss in obese subjects poorly controlled on insulin glargine and metformin. Titration of insulin glargine to optimal fasting glucose values is a prerequisite of success of this combination therapy.